2021
DOI: 10.1371/journal.pone.0253376
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in sleep and influence of the menstrual cycle on women’s sleep in junior endurance athletes

Abstract: Previous research shows that female athletes sleep better according to objective parameters but report worse subjective sleep quality than male athletes. However, existing sleep studies did not investigate variations in sleep and sleep stages over longer periods and have, so far, not elucidated the role of the menstrual cycle in female athletes’ sleep. To address these methodological shortcomings, we investigated sex differences in sleep and sleep stages over 61 continuous days in 37 men and 19 women and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
1
12
1
Order By: Relevance
“…Whilst there is high interest in sleep quality in sport science, due to its established link to recovery and performance [26], there is a paucity of research on MC-based changes in sleep within athletes. During menstrual bleeding and the follicular phase, female athletes spend more time in bed and more time in slow wave (deep) sleep compared to the luteal phase [27], which is in agreement with the preliminary findings in AFLW athletes in the current study. Home electroencephalography has demonstrated that female collegiate athletes had a significantly lower total sleep time, sleep efficiency and prolonged sleep latency during the first early follicular phase compared to the mid follicular phase.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst there is high interest in sleep quality in sport science, due to its established link to recovery and performance [26], there is a paucity of research on MC-based changes in sleep within athletes. During menstrual bleeding and the follicular phase, female athletes spend more time in bed and more time in slow wave (deep) sleep compared to the luteal phase [27], which is in agreement with the preliminary findings in AFLW athletes in the current study. Home electroencephalography has demonstrated that female collegiate athletes had a significantly lower total sleep time, sleep efficiency and prolonged sleep latency during the first early follicular phase compared to the mid follicular phase.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there were no significant differences found in the SDS or SDS categories by gender, sports type and sports events. These results were contradicted by the previous study, 29 where Hrozanova et al. found that female endurance athletes preferred to report poorer subjective sleep quality than male athletes.…”
Section: Discussioncontrasting
confidence: 57%
“…The possible reason for this difference was the fluctuations of female hormones and the side effects of the menstrual cycle. 29 However, information about female athletes’ menstrual cycle was not collected in this study and therefore cannot be interpreted. Besides, Rabin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep plays an important role in performance, injury rates, inflammation, and recovery [49]. While only one study in this review examined sleep disorder prevalence, it had a reasonably sized female cohort (n = 95) and the findings are supported by larger studies in both ultramarathon runners and general populations [49,[80][81][82]. A meta-analysis of 29 studies found that females were 40% more likely to suffer from insomnia than males [82].…”
Section: Healthmentioning
confidence: 77%
“…While only one study in this review examined sleep disorder prevalence, it had a reasonably sized female cohort (n = 95) and the findings are supported by larger studies in both ultramarathon runners and general populations [49,[80][81][82]. A meta-analysis of 29 studies found that females were 40% more likely to suffer from insomnia than males [82]. However, these studies largely relied on self-reported measures of sleep.…”
Section: Healthmentioning
confidence: 80%